2015
DOI: 10.3324/haematol.2014.117473
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of vorinostat and rituximab for treatment of newly diagnosed and relapsed/refractory indolent non-Hodgkin lymphoma

Abstract: Patient eligibilityPatients over the age of 18 with histologically or cytologically confirmed indolent non-Hodgkin lymphoma were eligible including: untreated, relapsed, or refractory follicular lymphomas of any grade, marginal zone B-cell lymphoma (nodal and extranodal), and mantle cell lymphoma. Patients may have had up to 4 prior regimens, not including steroids alone, rituximab alone, or local radiation. Treatment and evaluationOne cycle of therapy consisted of oral vorinostat 200 mg twice daily for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 20 publications
3
39
0
1
Order By: Relevance
“…The targeted agent that has been studied longest for its synergistic effect with vorinostat in MCL is rituximab. An experimental study using MCL cell lines demonstrated synergistic anti-MCL activity of vorinostat and rituximab [38], which was consistent with the results of clinical trials testing the efficacy of vorinostat with rituximab with or without a conventional regimen of cytotoxic chemotherapeutic drugs in patients with aggressive B-cell lymphomas [39][40][41]. The addition of rituximab to V-FND is a promising candidate for future clinical trials for relapsed or refractory MCL.…”
Section: Discussionsupporting
confidence: 73%
“…The targeted agent that has been studied longest for its synergistic effect with vorinostat in MCL is rituximab. An experimental study using MCL cell lines demonstrated synergistic anti-MCL activity of vorinostat and rituximab [38], which was consistent with the results of clinical trials testing the efficacy of vorinostat with rituximab with or without a conventional regimen of cytotoxic chemotherapeutic drugs in patients with aggressive B-cell lymphomas [39][40][41]. The addition of rituximab to V-FND is a promising candidate for future clinical trials for relapsed or refractory MCL.…”
Section: Discussionsupporting
confidence: 73%
“…Non‐chemotherapeutic approaches, such as rituximab and lenalidomide combinations (Fowler et al , ), alternative anti‐CD20 monoclonal antibodies (Negrea et al , ; Salles et al , ), BCL2 inhibitors (Roberts et al , ), HDAC inhbitors (Chen et al , ), PI3 kinase inhibitors (Gopal et al , ), immunomodulatory drugs (Fowler et al , ; Leonard et al , ), immunotherapies (Westin et al , ), or proteasome inhibitors (Evens et al , ), with or without rituximab, are promising. The role of rituximab maintenance therapy in LTBFL is unclear, with evidence from the RESORT trial indicating that maintenance treatment might be dispensable (Kahl et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Chiron and colleagues showed that inhibition of CDK4 with PD 0332991 (palbociclib) sensitizes ibrutinib-resistant lymphoma cells to ibrutinib in the absence of BTK mutations; however, use of PI3K inhibitors was more effective for treating cells carrying a BTK mutation (C481S) [144]. Similarly, in a recent trial with vorinostat and Rituximab, 33% of patients ( n = 3) achieved PR and ORR [145]. Additional clinical trials have been designed to evaluate the efficiency of CDK inhibitor alone and in combination for MCL (Table 3).…”
Section: Novel Drugs For MCL Based On Signaling Pathwaysmentioning
confidence: 99%